1969
DOI: 10.1002/aic.690150315
|View full text |Cite
|
Sign up to set email alerts
|

Newtonian jet stability: The role of air resistance

Abstract: The stability of high speed laminar Newtonian jets is studied as a function of ambient air pressure. For Weber numbers less than 5.3 (based on air density) air pressure has no effect on stability. Ambient viscosity, through the effect of shear stresses acting on the jet surface, gives rise to the maximum in the breakup curve. For large Weber numbers ambient pressure effects can alter, and eventually control, the appearance of the maximum.Liquid jets ejected from long capillaries break up into droplets in a man… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0
1

Year Published

1969
1969
2014
2014

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(27 citation statements)
references
References 7 publications
0
26
0
1
Order By: Relevance
“…In this theory, the strong instability arises from a large velocity difference U between the liquid and gas phases. However, several experimental observations (Fenn & Middleman 1969;Davies & Young-Hoon 1974;Phinney 1975;Hoyt & Taylor 1977;Arai, Shimizu & Hiroyasu 1985;Karasawa et al 1992;Wu, Miranda & Faeth 1995), including those shown in figure 1, indicate that aerodynamic effects on turbulent atomization are of secondary…”
Section: Introductionmentioning
confidence: 92%
“…In this theory, the strong instability arises from a large velocity difference U between the liquid and gas phases. However, several experimental observations (Fenn & Middleman 1969;Davies & Young-Hoon 1974;Phinney 1975;Hoyt & Taylor 1977;Arai, Shimizu & Hiroyasu 1985;Karasawa et al 1992;Wu, Miranda & Faeth 1995), including those shown in figure 1, indicate that aerodynamic effects on turbulent atomization are of secondary…”
Section: Introductionmentioning
confidence: 92%
“…But as it can be seen with a literature review there have been many different results. For example, Fenn and Middleman [3], working with jet velocities ranging between 2 m/s and 70 m/s, and ambient pressures within 7 hPa and 980 hPa, Weber numbers between 600 and 188000 and Reynolds numbers between 500 and 3000, concluded that the jet stability is affected by atmospheric pressure only when the atmospheric Weber 1 is greater than 5.3. Davies and Young [4] studied jets with a velocity of 11 m/s in air atmospheres from 100 hPa to 1000 hPa, a Weber number of 3800 and a Reynolds of number of 25000.…”
Section: Effect Of the Surrounding Medium On The Jet Coherencementioning
confidence: 99%
“…They found, among others, that the structure of the studied jets was affected by the density of the surrounding gas, but the jet velocity did not show a detectable consistent effect on it. Authors like Fenn and Middleman [3], Eddingfield and Albrecht [7], and McCarthy and Molloy [8] reported changes in the tendency of the behavior of the jet coherence according to the jet velocity. This can explain the variety on the results of the studies mentioned above (including even the independency between the jet structure and jet velocity for certain ranges).…”
Section: Effect Of the Surrounding Medium On The Jet Coherencementioning
confidence: 99%
“…Die gasseitige Reynolds-Zahl beträgt Re g = 379 und die flüssig-keitsseitige Re l = 1500, so dass die mittlere Gasgeschwindigkeit 5 % der Austrittsgeschwindigkeit des Strahls entspricht. Die gasseitige Weber-Zahl We g = 0,1 liegt deutlich unter der kritischen Grenze von We g,krit = 5,3, ab der eine Beeinflussung des Strahls durch die Gasströmung zu erwarten ist [19]. Die Lösungswärme des Ammoniaks bewirkt einen Temperaturanstieg, der in allen beschriebenen Experimenten kleiner als 1 K ist und somit für die Betrachtung vernachlässigt wird.…”
Section: Absorptionsexperimenteunclassified